Independent Sharia-Based Housing Financing Scheme: A Case Study of the Fictive Financing of PT Cahaya Mentari Pratama - Mohamad Nur Kholiq; Prawitra Thalib (Jurnal Ilmu Multidisiplin, 2025)
The role of Islamic banking institutions in terms of housing finance has attracted the attention of many people, especially in countries where the majority are Muslim. This is based on the fact that most people prefer Islamic bank financing to avoid the element of usury, including in home financing in Islamic banks. Given that as is well known, many non-bank developers based on a lot of public interest in Islamic home financing products carry out this financing. The purpose of writing this journal is expected to provide knowledge to the public in conducting sharia-based housing finance. In writing this journal using legal research methods, namely legal research. The result of this writing is that in principle, Sharia-based Housing Financing must require the role of Islamic financial institutions, both through Islamic banking institutions and non-Islamic banking.